Formulasi Mecaf Cookies Berbasis Tepung Mocaf dan Kacang Merah Sebagai Alternatif Snack Penderita Diabetes Melitus - Dwitantika, Bryan; Priawantiputri, Witri; Rahmat, Mamat; Sulaeman, Agus (Jurnal Gizi dan Dietetik, 2025)
According to the 2018 Basic Health Research (Riskesdas), the prevalence of diabetes mellitus in Indonesia reached 1,017,290 people, increasing from 6.9% to 8.5%. Individuals with diabetes mellitus benefit from having a regular eating schedule, which helps synchronize the body’s insulin response. Snacks is important role in preventing drops in blood sugar levels. Cookies can be a suitable snack alternative. This research utilized local food ingredients, namely mocaf flour and red bean flour. The study aimed to determine the effect of mocaf flour and red bean flour formulation on the quality of "Mecaf Cookies," focusing on organoleptic properties and proximate nutritional value, including dietary fiber. The research design was experimental, using three different formulations: F1 (80% mocaf flour : 20% red bean flour), F2 (60% mocaf flour : 40% red bean flour), and F3 (50% mocaf flour : 50% red bean flour). The product name “Mecaf Cookies” is an acronym derived from its ingredients: mocaf and red bean flours. Organoleptic properties were evaluated using a hedonic test involving 36 semi-trained panelists. Statistical analysis using the Kruskal-Wallis test showed no significant difference in color (ρ > α, 0.127), while there were significant differences in aroma (ρ < α, 0.007), taste (ρ < α, 0.000), texture (ρ < α, 0.002), and overall acceptance (ρ < α, 0.000), followed by Mann-Whitney tests for further analysis. Proximate and dietary fiber analysis conducted at the SIG Laboratory in Jakarta showed that a serving of Mecaf Cookies (3 pieces or 45 grams) contains 225 kcal of energy, 3.6 grams of protein, 12.6 grams of fat, 28 grams of carbohydrates, and 5.9 mg of dietary fiber. Key words: diabetes mellitus, snack, cookies, mocaf flour, red bean flour